2010
DOI: 10.1144/0070855
|View full text |Cite
|
Sign up to set email alerts
|

The breakup of the South Atlantic Ocean: formation of failed spreading axes and blocks of thinned continental crust in the Santos Basin, Brazil and its consequences for petroleum system development

Abstract: The occurrence of failed breakup basins and deepwater blocks of thinned continental crust is commonplace in the rifting and breakup of continents, as part of passive margin development. This paper examines the rifting of Pangaea-Gondwanaland and subsequent breakup to form the South Atlantic Ocean, with development of a failed breakup basin and seafloor spreading axis (the deepwater Santos Basin) and an adjacent deepwater block of thinned continental crust (the Sao Paulo Plateau) using a combination of 2D flexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 27 publications
1
59
0
Order By: Relevance
“…Despite the large number of studies on continental rifts and rifted continental margins, Prosser (1993);Steel, 1993;Notvedt et al (1995Notvedt et al ( , 2000; Ravnås and Steel et al (1998), there is still a lack of a unified understanding of the mechanical and thermal processes that control their extensional geometry Beaumont, 2007, Fletcher et al, 2013;Nestola et al, 2013;Scotchman et al, 2010). The common models for lithospheric stretching are reviewed in this section.…”
Section: Models Of Lithospheric Stretchingmentioning
confidence: 99%
“…Despite the large number of studies on continental rifts and rifted continental margins, Prosser (1993);Steel, 1993;Notvedt et al (1995Notvedt et al ( , 2000; Ravnås and Steel et al (1998), there is still a lack of a unified understanding of the mechanical and thermal processes that control their extensional geometry Beaumont, 2007, Fletcher et al, 2013;Nestola et al, 2013;Scotchman et al, 2010). The common models for lithospheric stretching are reviewed in this section.…”
Section: Models Of Lithospheric Stretchingmentioning
confidence: 99%
“…Although several studies have suggested that in the South Atlantic the evaporite layer near the continent-ocean boundary overlies exhumed mantle (Unterneher et al 2010;Scotchman et al 2010;Zalán et al 2011), some recently drilled boreholes targeting the pre-salt reservoirs near the continent-ocean boundary in the Santos Basin, offshore Brazil, sampled Early Cretaceous basalts (Mohriak, 2011).…”
Section: Rifting Evolution and Sedimentary Environments At Breakup Timementioning
confidence: 99%
“…The outermost highs in these basins have not been drilled and alternative interpretations of their origin have been proposed, including volcanic highs, Precambrian horsts, uplifted rifted blocks, and exhumed serpentinized mantle (Lentini et al 2010;Scotchman et al 2010;Unternehr et al 2010;Zalán et al 2011).…”
mentioning
confidence: 99%
“…Notably, recent major exploration discoveries in the deepwater Brazilian Santos Basin have taken the spotlight from turbidite reservoirs (Scotchman et al 2010). These resources are hosted in Late Barremian and Aptian non-marine microbial carbonates in the late syn-rift and sag sequences prior to deposition of the South Atlantic salt basin (Machado et al 2009;Wright & Racey 2009).…”
Section: Reservoirsmentioning
confidence: 99%
“…A recently identified potential example is described by Scotchman et al (2010), who postulate a prebreakup rift, oblique to the continental margin, in the Santos Basin, offshore Brazil, thought to have proceeded almost to oceanic status. (2) The possibility of polyphase faulting in any given rift event.…”
mentioning
confidence: 99%